A feasibility study of noninvasive prenatal diagnosis in facioscapulohumeral muscular dystrophy type 1 in a Chinese family - Qin, Yayun; Xu, Hui; Yang, Jingmin; Wu, Yiming; Li, Hui; Wang, Bo; Liu, Lijun; Ren, Ding; Xu, Runhong; Li, Manman; Zhang, Chengcheng; Song, Jieping (Frontiers in Genetics, 2022)
Objective: To demonstrate the feasibility of haplotype-based noninvasive prenatal diagnosis of Facioscapulohumeral Muscular Dystrophy type 1 (FSHD1). Methods: Bionano optical mapping was used to identify the D4Z4 structural variation of the genomic DNA sample from the proband affected with FSHD1. In addition, based on the technique of next generation sequencing, the pathogenic haplotype was determined by using trio strategy through genotyping his parents, and also fetal inheritance of paternal haplotypes was then deduced using the Hidden Markov Model. Results: Bionano optical mapping analysis revealed that the proband has only three D4Z4 repeats left in the 4q35 chromosomal region and a disease-permitting 4qA haplotype. The other normal allele of the proband contains 29 D4Z4 repeats and also a 4qA haplotype. The noninvasive cell-free fetal DNA (cffDNA)-based haplotype analysis suggested that the fetus inherited the pathogenic allele from his father and thus was predicted to be affected by FSHD1. In addition, Bionano optical mapping also demonstrated the presence of the pathogenic allele in the fetus by interrogating the genomic DNA from the amniotic fluid cells. Conclusion: Our study showed the cffDNA-based haplotyping was feasible for the noninvasive prenatal diagnosis of FSHD1, which is able to provide earlier testing results with a lower risk of miscarriage and infection than invasive techniques.